2013
DOI: 10.2174/1566524011313030012
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Expression and its Potential Role in Primary and Metastatic Breast Cancers

Abstract: Recently immunoglobulin G (IgG) was found to be produced by neoplasms and promote tumor growth in cancer cell lines and animal models. To investigate the pathophysiological significance of cancer-produced IgG in breast cancer, we examined the expressions of IgG in 68 breast cancers including 40 primary cancers without metastasis and 28 cancers with axillary lymph node metastases. IgG gene expression was detected in all these samples. We found that IgG-expressing cancer cells were predominantly located in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…We also found that lung cancers with lymph node metastasis had higher expression rate of IgG. Similar observations were made by Ma et al in breast cancers [29]. These observations suggest that IgG producing cancer cells may have disordered cell cycles and chromatin replication.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that lung cancers with lymph node metastasis had higher expression rate of IgG. Similar observations were made by Ma et al in breast cancers [29]. These observations suggest that IgG producing cancer cells may have disordered cell cycles and chromatin replication.…”
Section: Discussionsupporting
confidence: 91%
“…Blockade of cancerous IgG with antisense RNA or IgG antibody suppressed cancer cell growth and increased apoptosis [5], [26][28]. By detecting IgG expression in 142 esophagus cancers and 80 soft tissue tumors, and comparative analysis of IgG expression with pathological parameters, cancerous IgG was found to correlate with tumor grade and proliferative markers such as PCNA and ki-67 in cancers of the breast, esophagus and soft tissues [8], [11], [29]. These results suggest that cancerous IgG might play a role in regulating cancer growth.…”
Section: Introductionmentioning
confidence: 99%
“…These include cancer cells such as breast cancer cells, 1, 2, 3 colorectal cancer cells, 4, 5 prostate cancers cells, 6 papillary thyroid cancer cells 7 and soft tissue tumors, 8 human umbilical endothelial cells, 9 testicular spermatogenic cells, 10 epididymal epithelial cells, 10 human and mouse neurons 11, 12 and eyes. 13 It was reported that IgG secreted by human cancers promoted growth and survival of tumor cells.…”
mentioning
confidence: 99%
“…1 IgG detected in a wide variety of neoplasms was found to correlate with proliferation markers and tumor grades. 1, 3, 5 Furthermore, knockdown of the expression of heavy-chain genes of immunoglobulin isotypes through siRNA suppressed cancer cell growth in vitro and in vivo . 14 However, the regulatory mechanism of the above biological effects remains uncertain.…”
mentioning
confidence: 99%
“…Since CA215 is cancer-associated, elevated levels of CA215 in the human circulation may indicate active growth/proliferation or metastasis of cancer cells in the human body [1,2,5,11,[13][14][15][16][17][18][19][20]. Immunoassays using RP215 as a unique substitute for antibodies against cancerous immunoglobulins have been established for the quantitative determination of serum levels of CA215 [1].…”
mentioning
confidence: 99%